KAJIAN DAN EVALUASI BISNIS SENKUKO DI JAWA TIMUR - Alvy Mulyaningtyas, Wiwiek Harwiki, Nur Sayidah, (Jurnal Manajemen dan Keuangan, 2008)
At early 2006 Dinas Koperasi, Usaha Kecil, dan Menengah East Java had launched a program for Co-Operation called Senkuko (Sentra Perkulakan Koperasi). The goal of this program is to give the opportunity to Co-Operations in East Java to conduct modern ritel business. Senkuko would be managed by thirty party based on an appointment beetwen that party and Co-Operations. This cooperation is expected would be able to help Senkuko to achieve a good performance and transfer of knowledge and technology. Actually, Senkuko have bad fluctuating performance. On average, good performance of Senkuko were achieved only while grand launching. After that, Senkukoâs performance trend is decrease. This study find some problems. These problems are about stock management, distribution management, pricing, brand, sales target, commucation and financial statement. There are some recommendations on these problems including conduct independent audit, revise sales target, improve communication, stop blooding cash flow and make action plan properly vision and missions.Keyword : Senkuko, ritel modern, performance.